Fashion, history, museums : inventing the display of dress (2019)
It has become easy to become complacent about fashion exhibitions in museums. Their sheer number and extravagant scale have drowned out the skeptics who once questioned the place of fashion in the museum. Yearly, and even monthly, news media outlets report lists of the must-see fashion exhibitions worldwide, anticipating the avid interest of their readership. Richly illustrated reviews of the major retrospectives in global centers appear in academic journals and the mainstream media alike; catalogs are sold like coffee-table books. With their associated celebrity spectacle, their designer glamour, and their mystique of intimate history, it is tempting to take contemporary fashion exhibitions at face value. However, the display of historical fashion is not uninformed or insignificant. It does not merely reflect the technical possibilities, museal conventions, and aesthetic preferences of any given period; neither is it only a chance product of the combination of the resources of the museum and the embodiment of the subjective personal visions of the curatorial and design teams responsible for the exhibit. Far from being passively formed, it is a result of an active series of choices that have at their core particular assumptions about the role of historical dress in culture, then and now; moreover, this has wide-reaching consequences and significance. It is not only the experience and opinion of museum visitors that are affected but the practice of other museums changes in a cycle of emulation and visual echo; fashion history and theory as they written are also dependent on what the authors have seen. When Elizabeth Wilson, a pioneer of contemporary fashion theory, wrote about museum displays of dress being eerie, uncanny, and dead, she was referring to her experiences at the Victoria and Albert Museum’s (V&A) Costume Court (2010: 2); the contention colors her book Adorned in Dreams, first published in 1985, and many works on the topic published since. With its evidently fundamental influence on academic literature, therefore, documenting the actual practices, aims, and outcomes of fashion curation and, more specifically, of historical fashion curation is important. The research presented in this book is an overview of the possibilities for exhibitions of historical fashion as they have been realized over the last century across national boundaries; furthermore, it highlights the multiple ways in which the representations of fashion within the museum have also engaged with wider discourses within popular culture and academic writing on fashion’s role in society and culture more generally.